THE DEPRESSIVE AND ANXIETY SYMPTOMS AND PSYCHOLOGICAL DISTRESS AMONG INDONESIAN ADULTS DURING COVID-19 PANDEMIC - Sisilia Orlin; Felix Wijovi; Nadya Nathalia Evangelista; Stella Angelina; Devina Adella Halim; Audrey Hamdoyo; Timotius Ivan Hariyanto; Darien Alfa Cipta; Andree Kurniawan (Universitas Airlangga, 2023)
Introduction: COVID-19 outbreak has caused changes around the world with many polices remade to stop the spread of this virus since it started in 2019. Indonesia with the overall highest positive cases in South-East Asia has been challenged with prolonged restriction policy issued from early 2020 until now due to continuous increase of cases. This study aims to know the mental health of Indonesia citizens during early quarantine before it changed into restriction. Method: Indonesian version DASS-21 questionnaire was used in this cross-sectional study to assess Indonesian adults aged > 25 years old using an online platform from 22nd April, 2020 to 28th May, 2020, then analyzed using T-test and one-way ANOVA. Result: All participants have no depression and stress symptoms that meet the threshold for probable depression according to the DASS-21 instrument. On the other hand, 26.3% participants showed anxiety symptom with severity classified into mild (16.0%), moderate (8.9%), and severe (0.4%). Conclusion: This study also found relationship of depression, anxiety, and stress characteristic with gender, age marital status, and income in adults during pandemic. Where in this study shows male, younger age, unmarried status, and lower income people have higher scale of depression, anxiety, and stress characteristic. This finding may help Indonesia’s government and citizens to assess the restriction to mental health of Indonesian adults for further effective policy implementation.